Preparation method of high-molecular adhesive with super binding power

By applying specific polymer adhesives on the PET base film, the problem of insufficient bonding strength of existing adhesives under high temperature conditions is solved, and efficient sealing and flame retardant effects are achieved. It is suitable for power batteries and CCS battery wiring Application.

CN119463732AInactive Publication Date: 2025-02-18JIANGYIN SWIN ELECTRONICS NEW MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411820946.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-04-23
Filing Date
2024-12-11
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure CN119463732A_ABST
    Figure CN119463732A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a super-cohesive-force polymer adhesive, and relates to the technical field of polymer adhesives, the super-cohesive-force polymer adhesive comprises a product structure formed by coating an adhesive on a PET base film and using PET release for protection, the adhesive positioned on the middle layer is prepared from 27.481% by weight of MEK, 2.71% by weight of MCS, 6.42% by weight of cyclohexanone CYC, 6.32% by weight of Al (OH) 3, 7.8% by weight of FR-95 flame-retardant powder, 18% by weight of a mixed solution of X740 rubber and carboxy nitrile rubber, 12.64% by weight of 901 epoxy resin, 4.71% by weight of EP4000 resin, 20.62% by weight of a 550 resin pre-solution, 1.35% by weight of a South Asia THPA accelerator and 2.71% by weight of a curing agent 1081; compared with the prior art, the preparation method has the advantages that the X740 rubber is added into a pure epoxy resin rubber system, so that the traditional method of taking pure epoxy resin as a system is broken, the bonding strength of the prepared high-molecular adhesive finished product is higher, and the phosphorus-containing silicate is added into the FR-95 flame-retardant powder and is put into a grinding stirrer to be ground.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer adhesives, in particular to a method for preparing a super-adhesive polymer adhesive. Background Art

[0002] The present invention is mainly used in power batteries, internal heat insulation and flame retardant films, and is also used in CCS battery cables of batteries, and has the advantages of cost reduction, flame retardancy, insulation protection, temperature resistance and pressure resistance.

[0003] Ordinary adhesives with PET base film as the glue carrier and pure polyurethane as the main component have the following disadvantages: poor bonding strength, no flame retardancy, very brittle, and unable to achieve the sealing effect of temperature and pressure resistance;

[0004] The glass transition temperature is relatively low, and the use temperature is controlled between 80℃ and 120℃. When the temperature is higher than 120℃, the peel strength is greater. Ordinary adhesives with polyurethane as the main component need to be matured for 24 hours at a temperature of 50℃, but the resulting bonding strength is not large. For example, they cannot be used in power battery insulation films (when sandwiching aerogel, it is required to be pressed at a temperature of 80℃ and within 8 seconds, and the bonding strength is required to reach more than 1.2kg·f / cm, and the package is tight and leak-proof) or CCS battery cables. For this reason, we propose a preparation method for a super-adhesive polymer adhesive. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a high-molecular adhesive with super adhesion.

[0006] To solve the problems raised in the above background technology, the present invention provides the following technical solutions: a method for preparing a super-adhesive polymer adhesive, comprising a product structure formed by coating an adhesive on a PET base film and using a PET release film to protect the adhesive, wherein the adhesive located in the middle layer is prepared by weight of 27.481% butanone, 2.71% ethylene glycol methyl ether, 6.42% cyclohexanone CYC, 6.32% Al(OH)3, 7.8% FR-95 flame retardant powder, 18% X740 rubber and carboxyl nitrile rubber mixed solution, 12.64% 901 epoxy resin, 4.71% EP4000 resin, 20.62% 550 resin pre-solution, 1.35% Nan Ya THPA accelerator and 2.71% curing agent 1081, and the specific steps of the method for preparing the super-adhesive polymer adhesive are as follows:

[0007] Step 1, weigh X740 rubber and carboxyl nitrile rubber in a mass ratio of 4:3, mix them, add 80% by mass fraction of butanone solution and stir evenly, pour them into a mixer and stir at a stirring speed of 1000 r / min for 24 h±2 h to completely dissolve the rubber to obtain a mixed rubber pre-solution, wherein the solid content of the mixed rubber accounts for 19.5% to 20.5% of the mixed rubber pre-solution, and the viscosity of the mixed rubber pre-solution is 1000 cps±200 cps;

[0008] Step 2, weigh 550 epoxy resin and butanone in a mass ratio of 1:4, mix them evenly, pour them into a mixer and stir them at a stirring speed of 1000r / min for 10h±2h, and after stirring, prepare an epoxy resin pre-solution, the epoxy resin solid content of which is 18% to 20%, and the viscosity of the epoxy resin pre-solution is 1000cps±200cps;

[0009] Step 3, adding butanone, ethylene glycol methyl ether, CYC, Al(OH)3, FR-95 flame retardant powder, X740 rubber and carboxyl nitrile rubber mixed rubber pre-solution into a mixer in order and stirring, mixing all the added raw materials and stirring at a stirring speed of 1000 r / min for 3h to 5h to obtain an intermediate product;

[0010] Step 4: After the intermediate product is prepared, add 901 epoxy resin, EP4000 resin, 550 resin pre-solution and Nan Ya THPA accelerator into it in order, mix all the added raw materials with the intermediate product, and then stir at a stirring speed of 1200r / min for 8h±0.5h to obtain an adhesive mixture, the solid content of which accounts for 38% to 45% of the total mass of the adhesive mixture, and the viscosity of the adhesive mixture is 500cps±200cps;

[0011] Step 5, adding curing agent 1081 to the adhesive mixture and stirring and mixing, placing the mixture in a mixer and stirring at a stirring speed of 1200 r / min for 3 hours to obtain an adhesive product, wherein the solid content of the adhesive product accounts for 38% to 45% of the total mass of the adhesive product, and the viscosity of the adhesive product is 500 cps ± 200 cps;

[0012] Step 6: Lay the PET base film flat on a flat surface to ensure that the surface is clean and tidy. Apply the finished adhesive obtained in step 5 on the PET base film, place it in a drying oven and dry it at 150°C for 3 minutes. The thickness of the adhesive layer after drying is 30μm±3μm, and the thickness of the glue coating ranges from 3μm to 100μm.

[0013] As a further solution of the present invention: in the step 1, the temperature of mixing the X740 rubber and the carboxylated nitrile rubber is controlled to be 20° C. to 30° C., and after the X740 rubber and the carboxylated nitrile rubber are completely mixed, butanone is added and stirred.

[0014] As a further solution of the present invention: in the step 1, a rotational viscometer is used to measure the viscosity of the mixed rubber pre-solution, and the measurement temperature needs to be controlled between 25°C and 35°C.

[0015] As a further scheme of the present invention: in the step three, butanone, ethylene glycol methyl ether, CYC, Al(OH)3, FR-95 flame retardant powder, X740 rubber and carboxyl nitrile rubber mixed rubber pre-solution are added in sequence in small amounts and multiple times. When adding one substance at a time, it is necessary to completely mix it with the previous substance before adding the remaining substance for mixing and stirring. The stirring temperature needs to be controlled between 20°C and 30°C.

[0016] As a further solution of the present invention: in the step 4, after determining that the viscosity of the adhesive mixture meets the requirement, 901 epoxy resin, EP4000 resin, 550 resin pre-solution and Nan Ya THPA accelerator are added in small amounts and multiple times in sequence. After adding each substance, it is necessary to stir and mix it thoroughly, and then add the remaining substances and stir and mix them. The stirring temperature is controlled between 20°C and 30°C.

[0017] As a further solution of the present invention: in step six, the coating thickness of the actual adhesive product needs to be adjusted according to the thickness of the power battery, so that the bonding strength between the adhesive and the PET base film is required to reach above 1.2 kg·f / cm.

[0018] As a further solution of the present invention: after adding 550 rubber molecules with a glass transition temperature of -15°C, the X740 rubber molecules and the carboxyl nitrile rubber molecules are mutually fused and infiltrated under the action of Nan Ya THPA accelerator, and by adjusting and thickening the remaining additives, a cross-linking reaction occurs between the rubber molecules, thereby activating the activity of the adhesive.

[0019] As a further solution of the present invention: the FR-95 flame retardant powder added in proportion is a nano-scale flame retardant, the phosphorus-containing silicate is placed in a grinder at a speed of 1000r / min for stirring and grinding, and the ground phosphorus-containing silicate is added when the FR-95 flame retardant powder is added, so that its molecules are evenly mixed and penetrated with the adhesive molecules.

[0020] By adopting the above technical solution, compared with the prior art, the beneficial effects of the present invention are:

[0021] 1. The present invention breaks the traditional practice of using pure epoxy resin as the system by adding X740 rubber to the pure epoxy resin rubber system, so that the bonding strength of the obtained polymer adhesive product is higher. By adding phosphorus-containing silicate to the FR-95 flame retardant powder and grinding the phosphorus-containing silicate in a grinding mixer, the phosphorus-containing silicate molecules can be evenly mixed and penetrated with the adhesive molecules, so as to achieve the purpose of high-efficiency flame retardancy;

[0022] 2. The present invention adds Nan Ya THPA accelerator to make X740 rubber molecules and carboxyl nitrile rubber molecules fuse and penetrate each other, thus activating the activity of the adhesive. Since the adhesive and the adhesive molecules have good compatibility, the molecules can be reversely osmotic at room temperature, which plays a good sealing role when the adhesive surfaces are bonded to each other and when the aerogel is sandwiched. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Schematic diagram for comparing properties of finished adhesive products in embodiments of the present invention. DETAILED DESCRIPTION

[0024] The specific embodiments of the present invention are further described below in conjunction with the accompanying drawings. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0025] The invention discloses a method for preparing a high-molecular adhesive with super-adhesive force; the method comprises a product structure in which the adhesive is coated on a PET base film and protected by a PET release agent; the adhesive in the middle layer is prepared by 27.481% of butanone, 2.71% of ethylene glycol methyl ether, 6.42% of cyclohexanone CYC, 6.32% of Al(OH)3, 7.8% of FR-95 flame retardant powder, 18% of a mixed solution of X740 rubber and carboxyl nitrile rubber, 12.64% of 901 epoxy resin, 4.71% of EP4000 resin, 20.62% of a 550 resin pre-solution, 1.35% of a Nan Ya THPA accelerator and 2.71% of a curing agent 1081 by weight; the X740 rubber of the present application can be selected from existing nitrile rubber Carboxylated nitrile rubber can be selected from carboxylated nitrile rubber 1072; 550 epoxy resin can be selected from Epoxy resin;

[0026] The specific steps of a method for preparing a super-adhesive polymer adhesive are as follows:

[0027] Step 1, weigh X740 rubber and carboxyl nitrile rubber in a mass ratio of 4:3, mix them, add 80% by mass fraction of butanone solution and stir evenly, pour them into a mixer and stir at a stirring speed of 1000 r / min for 24 h±2 h to completely dissolve the rubber to obtain a mixed rubber pre-solution, wherein the solid content of the mixed rubber accounts for 19.5% to 20.5% of the mixed rubber pre-solution, and the viscosity of the mixed rubber pre-solution is 1000 cps±200 cps;

[0028] Step 2, weigh 550 epoxy resin and butanone in a mass ratio of 1:4, mix them evenly, pour them into a mixer and stir them at a stirring speed of 1000r / min for 10h±2h, and after stirring, prepare an epoxy resin pre-solution, the epoxy resin solid content of which is 18% to 20%, and the viscosity of the epoxy resin pre-solution is 1000cps±200cps;

[0029] Step 3, adding butanone, ethylene glycol methyl ether, CYC, Al(OH)3, FR-95 flame retardant powder, X740 rubber and carboxyl nitrile rubber mixed rubber pre-solution into a mixer in order and stirring, mixing all the added raw materials and stirring at a stirring speed of 1000 r / min for 3h to 5h to obtain an intermediate product;

[0030] Step 4: After the intermediate product is prepared, add 901 epoxy resin, EP4000 resin, 550 resin pre-solution and Nan Ya THPA accelerator into it in order, mix all the added raw materials with the intermediate product, and then stir at a stirring speed of 1200r / min for 8h±0.5h to obtain an adhesive mixture, the solid content of which accounts for 38% to 45% of the total mass of the adhesive mixture, and the viscosity of the adhesive mixture is 500cps±200cps;

[0031] Step 5, adding curing agent 1081 to the adhesive mixture and stirring and mixing, placing the mixture in a mixer and stirring at a stirring speed of 1200 r / min for 3 hours to obtain an adhesive product, wherein the solid content of the adhesive product accounts for 38% to 45% of the total mass of the adhesive product, and the viscosity of the adhesive product is 500 cps ± 200 cps;

[0032] Step 6: Lay the PET base film flat on a flat surface to ensure that the surface is clean and tidy. Apply the finished adhesive obtained in step 5 on the PET base film, place it in a drying oven and dry it at 150°C for 3 minutes. The thickness of the adhesive layer after drying is 30μm±3μm, and the thickness of the glue coating ranges from 3μm to 100μm.

[0033] In one embodiment of the present invention: in step 1, the temperature of mixing the X740 rubber and the carboxylated nitrile rubber is controlled to be 20° C. to 30° C., and after the X740 rubber and the carboxylated nitrile rubber are completely mixed, butanone is added and stirred.

[0034] In one embodiment of the present invention: in step 1, a rotational viscometer is used to measure the viscosity of the mixed rubber pre-solution, and the measurement temperature needs to be controlled between 25°C and 35°C.

[0035] In one embodiment of the present invention: in step three, butanone, ethylene glycol methyl ether, CYC, Al(OH)3, FR-95 flame retardant powder, X740 rubber and carboxyl nitrile rubber mixed rubber pre-solution are added in small amounts and multiple times in sequence. When adding one substance at a time, it is necessary to completely mix it with the previous substance before adding the remaining substance for mixing and stirring, and the stirring temperature needs to be controlled between 20°C and 30°C.

[0036] In one embodiment of the present invention: in step 4, after determining that the viscosity of the adhesive mixture meets the requirement, 901 epoxy resin, EP4000 resin, 550 resin pre-solution and Nan Ya THPA accelerator are added in small amounts and multiple times in sequence. After adding each substance, it is necessary to stir and mix it thoroughly, and then add the remaining substances and stir and mix them. The stirring temperature is controlled between 20°C and 30°C.

[0037] In one embodiment of the present invention: in step six, the actual coating thickness of the finished adhesive needs to be adjusted according to the thickness of the power battery, so that the bonding strength between the adhesive and the PET base film is required to reach 1.2 kg·f / cm or more.

[0038] In one embodiment of the present invention: after adding 550 rubber molecules with a glass transition temperature of -15°C, the X740 rubber molecules and the carboxyl nitrile rubber molecules are mutually fused and infiltrated under the action of Nan Ya THPA accelerator, and the cross-linking reaction occurs between the rubber molecules through the adjustment and thickening of the remaining additives, thereby activating the activity of the adhesive.

[0039] In one embodiment of the present invention: the FR-95 flame retardant powder added in proportion is a nano-scale flame retardant, the phosphorus-containing silicate is placed in a grinder at a speed of 1000r / min for stirring and grinding, and the ground phosphorus-containing silicate is added when the FR-95 flame retardant powder is added, so that its molecules are evenly mixed and penetrated with the adhesive molecules.

[0040] Embodiment 1

[0041] Take a mixing bucket and add X740 rubber and carboxyl nitrile rubber mixed in a mass ratio of 4:3. After mixing, add 80% butanone solution by mass and stir evenly. Then pour it into a mixer and stir at a stirring speed of 1000 r / min for 24h±2h. The rubber is completely dissolved to obtain a mixed rubber pre-solution. The solid content of the mixed rubber accounts for 19.5% to 20.5% of the mixed rubber pre-solution. The viscosity of the mixed rubber pre-solution is 1000cps±200cps. Weigh 550 epoxy resin and butanone in a mass ratio of 1:4, mix them evenly, pour them into a mixer and stir at a stirring speed of 1000 r / min for 10h. After stirring, an epoxy resin pre-solution is obtained. The solid content of the epoxy resin inside is 18% to 20%, and the viscosity of the epoxy resin pre-solution is 1000cps±200cps.

[0042] Take a stirring barrel and pour the prepared mixed rubber pre-solution and epoxy resin pre-solution into it for stirring. During stirring, add butanone, ethylene glycol methyl ether, CYC, Al(OH)3, FR-95 flame retardant powder, and X740 rubber and carboxyl nitrile rubber mixed rubber pre-solution in sequence. When adding one substance at a time, it is necessary to mix it with the previous substance completely before adding the remaining substances for mixing and stirring. The stirring speed is 1200r / min, the stirring time is 3h, and the stirring temperature needs to be controlled between 20℃ and 30℃. After the stirring is completed, add 90 1Epoxy resin, EP4000 resin, 550 resin pre-solution and Nan Ya THPA accelerator, after adding each substance, it is necessary to stir and mix it completely, and then add the remaining substances and stir and mix them. The stirring speed is 1200r / min, the stirring time is 8h, and the stirring temperature is controlled between 20℃ and 30℃. After stirring, continue to add curing agent 1081, and stir at a stirring speed of 1200r / min for 3h to obtain a finished adhesive. The solid content in the finished product accounts for 38% to 45% of the total mass of the finished adhesive, and the viscosity of the finished adhesive is 500cps.

[0043] Embodiment 2

[0044] Take a mixing bucket and add X740 rubber and carboxyl nitrile rubber mixed in a mass ratio of 4:3. After mixing, add 80% butanone solution by mass and stir evenly. Then pour it into a mixer and stir at a stirring speed of 1000 r / min for 24h±2h. The rubber is completely dissolved to obtain a mixed rubber pre-solution. The solid content of the mixed rubber accounts for 19.5% to 20.5% of the mixed rubber pre-solution. The viscosity of the mixed rubber pre-solution is 1000cps±200cps. Weigh 550 epoxy resin and butanone in a mass ratio of 1:4, mix them evenly, pour them into a mixer and stir at a stirring speed of 1000 r / min for 10h. After stirring, an epoxy resin pre-solution is obtained. The solid content of the epoxy resin inside is 18% to 20%, and the viscosity of the epoxy resin pre-solution is 1000cps±200cps.

[0045] Take a stirring barrel and pour the prepared mixed rubber pre-solution and epoxy resin pre-solution into it for stirring. During stirring, add butanone, ethylene glycol methyl ether, CYC, Al(OH)3, FR-95 flame retardant powder, and X740 rubber and carboxyl nitrile rubber mixed rubber pre-solution in sequence. When adding one substance at a time, it is necessary to mix it with the previous substance completely before adding the remaining substances for mixing and stirring. The stirring speed is 1200r / min, the stirring time is 4h, and the stirring temperature needs to be controlled between 20℃ and 30℃. After stirring, add 90 1Epoxy resin, EP4000 resin, 550 resin pre-solution and Nan Ya THPA accelerator, after adding each substance, it is necessary to stir and mix it completely, and then add the remaining substances and stir and mix them. The stirring speed is 1200r / min, the stirring time is 8h, and the stirring temperature is controlled between 20℃ and 30℃. After stirring, continue to add curing agent 1081, and stir at a stirring speed of 1200r / min for 3h to obtain a finished adhesive. The solid content in the finished product accounts for 38% to 45% of the total mass of the finished adhesive, and the viscosity of the finished adhesive is 600cps.

[0046] Embodiment 3

[0047] Take a mixing bucket and add X740 rubber and carboxyl nitrile rubber mixed in a mass ratio of 4:3. After mixing, add 80% butanone solution by mass and stir evenly. Then pour it into a mixer and stir at a stirring speed of 1000 r / min for 24h±2h. The rubber is completely dissolved to obtain a mixed rubber pre-solution. The solid content of the mixed rubber accounts for 19.5% to 20.5% of the mixed rubber pre-solution. The viscosity of the mixed rubber pre-solution is 1000cps±200cps. Weigh 550 epoxy resin and butanone in a mass ratio of 1:4, mix them evenly, pour them into a mixer and stir at a stirring speed of 1000 r / min for 10h. After stirring, an epoxy resin pre-solution is obtained. The solid content of the epoxy resin inside is 18% to 20%, and the viscosity of the epoxy resin pre-solution is 1000cps±200cps.

[0048] Take a stirring bucket and pour the prepared mixed rubber pre-solution and epoxy resin pre-solution into it for stirring. During stirring, add butanone, ethylene glycol methyl ether, CYC, Al(OH)3, FR-95 flame retardant powder, and X740 rubber and carboxyl nitrile rubber mixed rubber pre-solution in sequence. When adding one substance at a time, it is necessary to mix it with the previous substance completely before adding the remaining substances for mixing and stirring. The stirring speed is 1200r / min, the stirring time is 5h, and the stirring temperature needs to be controlled between 20℃ and 30℃. After stirring, add 901 in sequence. Epoxy resin, EP4000 resin, 550 resin pre-solution and Nan Ya THPA accelerator, after adding each substance, it is necessary to stir and mix it thoroughly, and then add the remaining substances and stir and mix them. The stirring speed is 1200r / min, the stirring time is 8.5h, and the stirring temperature is controlled between 20℃ and 30℃. After stirring, continue to add curing agent 1081, and stir at a stirring speed of 1200r / min for 3h to obtain a finished adhesive. The solid content in the finished product accounts for 38% to 45% of the total mass of the finished adhesive, and the viscosity of the finished adhesive is 700cps.

[0049] Comparative ratio,

[0050] The polymer adhesive is prepared by using a polymer adhesive and a preparation method thereof provided in a patent document with application publication number CN 109266250A and titled “a polymer adhesive and a preparation method thereof”.

[0051] The PET base films were divided into four groups: A, B, C and D. The polymer adhesives prepared in the examples and comparative examples were used to coat the PET base films. The specific coating steps were as follows:

[0052] Group A: The PET base film was coated with the adhesive product prepared in Example 1, with a coating thickness of 50 μm, a lamination time of 6 s, and a aging time of 12 h;

[0053] Group B: The PET base film was coated with the adhesive product prepared in Example 2, with a coating thickness of 80 μm, a lamination time of 7 seconds, and a aging time of 12 hours;

[0054] Group C: The PET base film was coated with the adhesive product prepared in Example 3, with a coating thickness of 100 μm, a lamination time of 8 s, and a aging time of 12 h;

[0055] Group D: The PET base film was coated with the finished polymer adhesive prepared in the comparative example, with a coating thickness of 50 μm, a lamination time of 8 s, and a aging time of 24 h.

[0056] The peeling test was used to test the bonding strength of the coated PET base films of groups A, B, C and D, and the UL94 grade test was used to test the flame retardancy of the coated PET base films. The test results are shown in the attached Figure 1 .

[0057] The PET base film is protected by a BOPP film after coating, and the BOPP film can be torn off when in use.

[0058] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the scope of protection of the present invention.

[0059] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0060] The above contents are merely examples and explanations of the present invention. Various modifications or additions to the specific embodiments described or replacements in similar ways by technicians in the technical field shall fall within the protection scope of the present invention as long as they do not deviate from the invention or exceed the scope defined by the claims.

[0061] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a super-adhesive polymer adhesive, comprising coating the adhesive on a PET base film and using a PET release film to protect the product structure, characterized in that: The adhesive in the middle layer is prepared by weight of 27.481% butanone, 2.71% ethylene glycol methyl ether, 6.42% cyclohexanone CYC, 6.32% Al(OH)3, 7.8% FR-95 flame retardant powder, 18% X740 rubber and carboxyl nitrile rubber mixed solution, 12.64% 901 epoxy resin, 4.71% EP4000 resin, 20.62% 550 resin pre-solution, 1.35% Nan Ya THPA accelerator and 2.71% curing agent 1081. The preparation method of the super-adhesive polymer adhesive has the following specific steps: Step 1, weigh X740 rubber and carboxyl nitrile rubber in a mass ratio of 4:3, mix them, add 80% by mass fraction of butanone solution and stir evenly, pour them into a mixer and stir at a stirring speed of 1000 r / min for 24 h±2 h to completely dissolve the rubber to obtain a mixed rubber pre-solution, wherein the solid content of the mixed rubber accounts for 19.5% to 20.5% of the mixed rubber pre-solution, and the viscosity of the mixed rubber pre-solution is 1000 cps±200 cps; Step 2, weigh 550 epoxy resin and butanone in a mass ratio of 1:4, mix them evenly, pour them into a mixer and stir them at a stirring speed of 1000r / min for 10h±2h, and after stirring, prepare an epoxy resin pre-solution, the epoxy resin solid content of which is 18% to 20%, and the viscosity of the epoxy resin pre-solution is 1000cps±200cps; Step 3, adding butanone, ethylene glycol methyl ether, CYC, Al(OH)3, FR-95 flame retardant powder, X740 rubber and carboxyl nitrile rubber mixed rubber pre-solution into a mixer in order and stirring, mixing all the added raw materials and stirring at a stirring speed of 1000 r / min for 3h to 5h to obtain an intermediate product; Step 4: After the intermediate product is prepared, add 901 epoxy resin, EP4000 resin, 550 resin pre-solution and Nan Ya THPA accelerator into it in order, mix all the added raw materials with the intermediate product, and then stir at a stirring speed of 1200r / min for 8h±0.5h to obtain an adhesive mixture, the solid content of which accounts for 38% to 45% of the total mass of the adhesive mixture, and the viscosity of the adhesive mixture is 500cps±200cps; Step 5, adding curing agent 1081 to the adhesive mixture and stirring and mixing, placing the mixture in a mixer and stirring at a stirring speed of 1200 r / min for 3 hours to obtain an adhesive product, wherein the solid content of the adhesive product accounts for 38% to 45% of the total mass of the adhesive product, and the viscosity of the adhesive product is 500 cps ± 200 cps; Step 6: Lay the PET base film flat on a flat surface to ensure that the surface is clean and tidy. Apply the finished adhesive obtained in step 5 on the PET base film, place it in a drying oven and dry it at 150°C for 3 minutes. The thickness of the adhesive layer after drying is 30μm±3μm, and the thickness of the coating is between 3μm and 100μm. In the step 1, the temperature of mixing the X740 rubber and the carboxyl nitrile rubber is controlled to 20°C to 30°C. After the X740 rubber and the carboxyl nitrile rubber are completely mixed, butanone is added and stirred. In the step 1, a rotational viscometer is used to measure the viscosity of the mixed rubber pre-solution, and the measurement temperature needs to be controlled between 25°C and 35°C. In the step 3, a small amount of Add butanone, ethylene glycol methyl ether, CYC, Al(OH)3, FR-95 flame retardant powder and X740 rubber and carboxyl nitrile rubber mixed rubber pre-solution in sequence for multiple times. When adding one substance at a time, it is necessary to completely mix it with the previous substance before adding the remaining substances for mixing and stirring. The stirring temperature needs to be controlled between 20°C and 30°C. In the step 4, after the viscosity of the adhesive mixture is determined to meet the requirements, 901 epoxy resin, EP4000 resin, 550 resin pre-solution and Nan Ya THPA accelerator are added in small amounts and multiple times in sequence. After adding a single substance, it needs to be completely stirred and mixed, and then the remaining substances are added for stirring and mixing. The stirring temperature is controlled between 20°C and 30°C.

2. The method for preparing a super-adhesive polymer adhesive according to claim 1, characterized in that: In step six, the actual coating thickness of the finished adhesive needs to be adjusted according to the thickness of the power battery, so that the bonding strength between the adhesive and the PET base film reaches above 1.2 kg·f / cm.

3. The method for preparing a super-adhesive polymer adhesive according to claim 1, characterized in that: After adding 550 rubber molecules with a glass transition temperature of -15°C, the X740 rubber molecules and carboxyl nitrile rubber molecules are fused and penetrated with each other under the action of Nan Ya THPA accelerator. Through the adjustment and thickening of the remaining additives, cross-linking reaction occurs between the rubber molecules, thereby activating the activity of the adhesive.

4. The method for preparing a super-adhesive polymer adhesive according to claim 1, characterized in that: The FR-95 flame retardant powder added in proportion is a nano-scale flame retardant. The phosphorus-containing silicate is placed in a grinder at a speed of 1000r / min for stirring and grinding. When adding the FR-95 flame retardant powder, the ground phosphorus-containing silicate is added to make its molecules evenly mixed and penetrated with the adhesive molecules.

Citation Information

Patent Citations

  • Low-halogen single-component flame-retardant epoxy adhesive

    CN102181252A